"Hello, hello—it's English I speak!": a qualitative exploration of patients' understanding of the science of clinical trials. Issue 11 (3rd November 2005) - Stead, M; Eadie, D; Gordon, D; Angus, K
Abstract : Informed consent may be seriously compromised if patients fail to understand the experimental nature of the trial in which they are participating. Using focus groups, the authors explored how prospective trial participants interpret and understand the science of clinical trials by using patient information sheets relative to their medical condition. An opportunity was provided to hear in the patients' own words how they interpret the information and why there is variable understanding. Respondents struggled to comprehend the meaning and purpose of concepts such as randomisation and double blinding, and found them threatening to their ideas of medical care. Suggestions are made about how to improve the national guidelines on written information for trial participants and pretesting of the information sheets is advocated.